(untitled) (Journal of Computational Mathematics, 2007)
In this paper, three n-rectangle nonconforming elements are proposed with n3. They are the extensions of well-known Morley element, Adini element and Bogner-Fox-Schmit element in two spatial dimensions to any higher dimensions respectively. These elements are all proved to be convergent for a model biharmonic equation in n dimensions.